PENGARUH GAYA KEPEMIMPINAN, DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT SARI RAMBUT DI ABUAN BANGLI - Ngakan Nyoman Bagus Putra Legawa; Ni Putu Cempaka Dharmadewi Atmaja; I Nengah Suardhika (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
The population in this study were 50 employees of PT Sari Rambut Abuan Bangli. Regarding the sample, the sample in this study consisted of 50 people who were determined using the census method or saturated sample. This research uses a number of data collection methods, both primary data and secondary data consisting of observation, interviews, questionnaires and documentation studies. To analyze the data, this research used five methods, including research instrument testing, classical assumption testing, multiple regression analysis, determination analysis, and t test. The research results show that Leadership Style, Work Discipline and Work Motivation have a positive and significant effect on employee performance at PT Sari Rambut Abuan Bangli. This means that the better these three factors are, the better the performance of PT Sari Rambut Abuan Bangli employees will be.